The Pub and the People. A Worktown Study by Mass Observation. (24th August 2020) - MacGregor, Susanne
Abstract : Mass Observation was an independent social research organization which, between 1937 and 1949, documented the attitudes, opinions and everyday lives of the British people, using a combination of anthropological fieldwork, opinion surveys and written testimony. The Pub and the People is a classic text for its distinctly sociological approach, seeing patterns of drinking and socializing in context, rather than focusing primarily on pathological consequences. The main conclusions were that the pub is a living social organism and that the traditional approach of British sociology which, Mass Observation argued, focused on 'the drink problem' and the links between alcohol, crime and delinquency, failed to take account of the full social context. Mass Observation's focus on the pub as a place anticipates themes taken up in work on alcohol in cultural geography. Later alcohol researchers and epidemiologists have continued this orientation, recognizing the importance of physical and social environments in relation to alcohol consumption. Other studies have built on the MO initiative by looking at how drug and alcohol consumption links to identity, friendship and sociality or at the connections between intoxication and pleasure. The value of this classic text is that it reminds us that paying attention to the social context is not just a useful supplement, but absolutely central to understanding the use of alcohol or drugs.